Pleural Effusion Associated with Hepatitis A - Kurt, A. Nese Citak; Bulut, Yasemin; Turgut, Mehmet; Akarsu, Saadet; Yilmaz, Erdal; Poyrazglu, Gamze; Aygun, A. Denizmen (Aves Yayincilik, Ibrahim Kara, 2008)
Hepatitis A is a very prevalent infection, especially in developing countries and one of its rare extra hepatic complications is pleural effusion. In this article, a child who had an unusual presentation of hepatitis A with pleural effusion was reported.
Keywords: Hepatitis A; pleural effusion; child